2004
DOI: 10.1074/jbc.m310405200
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-like Growth Factor 1 Receptor Induces Physiological Heart Growth via the Phosphoinositide 3-Kinase(p110α) Pathway

Abstract: Insulin-like growth factor 1 (IGF1) was considered a potential candidate for the treatment of heart failure. However, some animal studies and clinical trials have questioned whether elevating IGF1 chronically is beneficial. Secondary effects of increased serum IGF1 levels on other tissues may explain these unfavorable results. The aim of the current study was to examine the role of IGF1 in cardiac myocytes in the absence of secondary effects, and to elucidate downstream signaling pathways and transcriptional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
325
2
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(365 citation statements)
references
References 84 publications
19
325
2
6
Order By: Relevance
“…Interestingly, IGF1R RNA levels were elevated in KO-AL mice in comparison to N-AL and also in young, 3-month-old KO mice, while hGH transgenic mice had reduced level of IGF1R message. Because IGF1R can activate IRS1 and IRS2 just like IR, this can explain higher levels of these substrates in young KO mice in which IR RNA levels were not elevated (42). Study of IGF1R transgenic mice showed that over expressed IGF1R can cause enlargement of the heart (42).…”
Section: Insulin-like Growth Factor-1 and Insulin-like Growth Factor-mentioning
confidence: 99%
“…Interestingly, IGF1R RNA levels were elevated in KO-AL mice in comparison to N-AL and also in young, 3-month-old KO mice, while hGH transgenic mice had reduced level of IGF1R message. Because IGF1R can activate IRS1 and IRS2 just like IR, this can explain higher levels of these substrates in young KO mice in which IR RNA levels were not elevated (42). Study of IGF1R transgenic mice showed that over expressed IGF1R can cause enlargement of the heart (42).…”
Section: Insulin-like Growth Factor-1 and Insulin-like Growth Factor-mentioning
confidence: 99%
“…The PI3K pathway was documented to regulate a number of physiological functions, including cell growth, survival and actin cytoskeleton rearrangement [57]. It was documented to be involved in a physiological hypertrophy of cardiomyocytes [58,59] as well as in the response of endothelial cells [60], keratinocytes and epithelial cells to stimulation with DC fields [61]. In activated platelets, PI3-kinase associates with cytoskeleton when significant actin polymerization occurs [62].…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…In addition, IGF1R, an established factor in cardiac hypertrophy, is overexpressed in hypertrophic heart mediating the hypertrophic pathology process. In particular, it has been shown that the short-term activation of IGF signaling pathway promotes physiologic growth, whereas sustained hyperactivation leads to the development of pathologic hypertrophy and HF [36,37]. Interestingly, we observed that the expression of IGF-1R and myocardial hypertrophy in SD heart, are lower than those of HDF heart, suggesting that SD diet protects the heart from obesity dependent hypertrophy.…”
Section: Discussionmentioning
confidence: 56%